INFLUENCE OF SIZE EFFECT ON EVALUATION OF TENSILE PROPERTIES USING SMALL PUNCH TEST (MT) - WANG WuLin; XU Tong; ZHONG JiRu; GUAN KaiShu; LIU Gang (Jixie qiangdu)
In order to explore the effect of the specimen size on results of small punch test（SPT）, SPT was conducted on Incoloy 800H and low alloy steel 3Cr1MoV using various specimen thicknesses of 100～500 μm, and a database of force-deflection curves and true stresses were created for various specimen thicknesses by Ludwig hardening model and finite element method. True stress-plastic strain curves of different specimen sizes were acquired based on the database and SPT experimental curves. The strength properties of the studied materials were predicted through these true stress-plastic strain curves. Meanwhile, the relationship between flow stresses, strength properties and specimen size was obtained. The results show that tensile properties of Incoloy 800H increase gradually with the decrease of sample thicknesses, while sample sizes have a slightly influence on tensile properties of 3Cr1MoV. The different responses of tensile properties to thicknesses were discussed, which provides a basis for the selection and design of sample thickness when SPT is employed to predict tensile properties.